PENGARUH POST WELD HEAT TREATMENT TERHADAP KEKUATAN TARIK, KETANGGUHAN DAN KOROSI SAMBUNGAN PIPA LAS ERW LONGITUDINAL API 5L X-46 - , HERY TRISTIJANTO, Mochammad Noer Ilman, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Steel API 5L X-46 is a low alloysteel which is commonly used as material for high-pressure oil pipeline to transport LNG and crude oil. To fullfil theseoperating conditions pipeline is required to have a high tensile strength, resistance to corrosion due to hydrogen or an acid environment and good weldability. One of the welding technique for oil and gas pipelines is electric resistance welding (ERW). According to API, welded joints for oils and gases pipelines must have requirements, such as toughness of 27 J at 0º Cand hardness of not more than 22 HRC (248 VHN) to avoid the occurrence of sulfide stress cracking (SSC). To fulfill these requirements, in this research will carried out post weld heat treatment (PWHT). In this study PWHT was carried out at various temperatures of 450ºC, 550ºC and 650ºC with constant holding time of 1 hour followed by cooling in a furnace. Micro-structure analysis results show that the steel pipe of API 5L X-46 base metal and HAZ regions are composed by ferrite and pearlite phases, while the weld center is composed of bainite phase. PWHT reduces hardness and tensile strength, improves corrosion resistance and impact toughness. OptimumtemperaturePWHT is a achieved at the temperature of 550ºC.